Hydrogen evolution reaction on glassy carbon electrode modified with titanyl phthalocyanines - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
In this work, electrocatalytic activities of titanyl phthalocyanines coated on the glassy carbon working electrode(GCE) were investigated for hydrogen evolution reaction by cyclic voltammetry and chronoamperometry. Multi-electron, reversible, diffusion controlled, and metal-based reduction properties of the complexes show possible application as an electrocatalyst for hydrogen evolution reaction in aqueous solution. The complexes are easily electrodeposited on the glassy carbon electrode during the repetitive cycles, a very useful feature for application in fabrication of thin films. It is shown that especially catecholatooctakis(2-dimethylaminoethylsulfanyl phthalocyaninato) titanium(IV) and octakis(2-dimethylaminoethylsulfanyl phthalocyaninato) titanium(IV) derivatives electrodeposited on GCE have significant catalytic activities towards hydrogen evolution reaction. Electrocatalytic activities change irregularly with the pH of the solution. Moreover, the catalytic activity of the complexes enhanced significantly, when the complexes were incorporated into the Nafion polymeric matrix. Octakis(2-dimethylaminoethylsulfanyl phthalocyaninato) titanium(IV) incorporated into Nafion polymeric matrix decreases the overpotential of hydrogen evolution reaction on the glassy carbon electrode upto 0.32 V with augmenting hydrogen discharge current. (C) 2009 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: Titanyl; Phthalocyanine; Hydrogen evolution reaction; Electrocatalyst; Electrodeposition; ELECTROCATALYTIC ACTIVITY; COBALT; REDUCTION; CATALYSIS; TITANYLPHTHALOCYANINES; OXIDATION; COMPLEXES